The decline in child mortality: a reappraisal - Omar B. Ahmad; Alan D. Lopez; Mie Inoue (The World Health Organization, 2000)
The present paper examines, describes and documents country-specific trends in under-five mortality rates (i.e., mortality among children under five years of age) in the 1990s. Our analysis updates previous studies by UNICEF, the World Bank and the United Nations. It identifies countries and WHO regions where sustained improvement has occurred and those where setbacks are evident. A consistent series of estimates of under-five mortality rate is provided and an indication is given of historical trends during the period 1950-2000 for both developed and developing countries. It is estimated that 10.5 million children aged 0-4 years died in 1999, about 2.2 million or 17.5% fewer than a decade earlier. On average about 15% of newborn children in Africa are expected to die before reaching their fifth birthday. The corresponding figures for many other parts of the developing world are in the range 3-8% and that for Europe is under 2%. During the 1990s the decline in child mortality decelerated in all the WHO regions except the Western Pacific but there is no widespread evidence of rising child mortality rates. At the country level there are exceptions in southern Africa where the prevalence of HIV is extremely high and in Asia where a few countries are beset by economic difficulties. The slowdown in the rate of decline is of particular concern in Africa and South-East Asia because it is occurring at relatively high levels of mortality, and in countries experiencing severe economic dislocation. As the HIV/AIDS epidemic continues in Africa, particularly southern Africa, and in parts of Asia, further reductions in child mortality become increasingly unlikely until substantial progress in controlling the spread of HIV is achieved.